Analysis of clinicoradiological parameters following fixation of paediatric supracondylar humerus fractures with three lateral pins - Daga, Saurabh; Sarkar, Pushpal; Kumar Banka, Paras (International Journal of Research in Orthopaedics, 2019)
Background: Supracondylar humerus fractures are one of the commonest fractures encountered in children. This fracture has been managed both conservatively with a long arm plaster and operatively by fixing with Kirschner wires. Debate still remains regarding the pin configuration to be used for fracture stabilisation. This study analyses the clinical and radiological parameters following fixation of supracondylar humerus fractures in paediatric patients with three lateral pins. Methods: It is a prospective study with 30 patients conducted between April 2016 and September 2016 conducted in Medical College and Hospital, Kolkata. All the said patients underwent closed reduction and percutaneous pinning with three laterally placed divergent kirschner wires. Results: Most of the patients in this study had clinicoradiological parameters well within normal limits, barring a few. The baumann’s angle was well within normal limits in these cases as found in subsequent follow-ups. Conclusions: In this study, it was found that lateral pinning can be safely employed for fixing supracondylar humerus fractures in children with lesser chances of iatrogenic ulnar nerve palsy which was encountered with crossed pin configuration.